Diagnosis of Thymic Clear Cell Carcinoma by Cytology - Seema A. Lale; Patricia G. Tiscornia-Wasserman; Mohamed Aziz (Case Reports in Pathology)
Clear cell carcinoma of the thymus is a rare tumor. Few cases of clear-cell carcinoma of thymus have been documented (Truong et al., 1990 and Wolfe III et al., 1983). All these cases were diagnosed by histopathological examination of the tissue. Diagnosis of thymic clear cell carcinoma on cytology is extremely challenging. Here we report the first case of thymic clear cell carcinoma diagnosed by cytological examination of the pericardial fluid with the help of immunocytochemistry. Differential diagnosis included adenocarcinoma, mesothelioma, and thymic clear cell carcinoma. Thymic carcinoma with clear cell features has an aggressive clinical behavior including our case, where it was already metastasized at the time of presentation.